Pengaruh Pendekatan Etnosains melalui Model Problem Basedlearning terhadap Kemampuan Literasi Sains Padamateri Larutan Penyangga - Aulia Sanova; Affan Malik; H.R Yuniarccih S (Postgraduate, University of Mataram, 2023)
The aim of this study was to see the impact of the ethnoscience approach with a problem-based learning model on students' scientific reading skills of buffer solution material in class XI SMA. N 3 Jambi City. The approach used in this study is a quantitative one using a quasi-experimental design with a pre-test design for a first group to test first. The instrument used in this study was an essay test consisting of 9 questions and an assessment tool for student activities as supporting data. The results of the data analysis show that the use of an ethnographic approach with a problem-based learning model has an effect on students' scientific reading skills, as shown by an increase in the average results. average of the test before and after the test, i.e. 51.4% - 76.4%. Based on the obtained data, the result of tcount calculation is 10,4264 and t-table is 2.1098 with actual level = 5%. Â